2008
DOI: 10.1182/blood-2007-10-117820
|View full text |Cite
|
Sign up to set email alerts
|

Steel factor coordinately regulates the molecular signature and biologic function of hematopoietic stem cells

Abstract: Hematopoietic stem cells (HSCs) regenerated in vivo display sustained differences in their self-renewal and differentiation activities. Variations in Steel factor (SF) signaling are known to affect these functions in vitro, but the cellular and molecular mechanisms involved are not understood. To address these issues, we evaluated highly purified HSCs maintained in single-cell serum-free cultures containing 20 ng/mL IL-11 plus 1, 10, or 300 ng/mL SF. Under all conditions, more than 99% of the cells traversed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 54 publications
(84 reference statements)
6
61
1
1
Order By: Relevance
“…Hence the purity of this type of HSC in the E-SLAM fraction of adult BM was 43% ( Figure 2B). These values are much higher than we previously reported for other powerful HSC isolation strategies (eg, CD45 mid Rho Ϫ SP cells 12,17 and E-Rho Ϫ cells 34 ). Secondary mice transplanted with BM cells harvested individually from 4 primary mice that had each been repopulated with a single adult BM E-SLAM cell more than 26 weeks before confirmed that, in each case, progeny HSCs had been generated from the original input E-SLAM cell (data not shown).…”
Section: Selective Purification Of Hscs With Durable Self-renewal Frocontrasting
confidence: 60%
See 2 more Smart Citations
“…Hence the purity of this type of HSC in the E-SLAM fraction of adult BM was 43% ( Figure 2B). These values are much higher than we previously reported for other powerful HSC isolation strategies (eg, CD45 mid Rho Ϫ SP cells 12,17 and E-Rho Ϫ cells 34 ). Secondary mice transplanted with BM cells harvested individually from 4 primary mice that had each been repopulated with a single adult BM E-SLAM cell more than 26 weeks before confirmed that, in each case, progeny HSCs had been generated from the original input E-SLAM cell (data not shown).…”
Section: Selective Purification Of Hscs With Durable Self-renewal Frocontrasting
confidence: 60%
“…However, to obtain high HSC purities, additional elements are required, and these typically differ to accommodate the differing phenotypic characteristics of fetal and adult HSCs 14,30,31 caused by their different cycling status. 14,31 In preliminary studies, we found that a high expression of EPCR, a powerful discriminator of adult BM HSCs, 11 was stable on HSCs that had been proliferating in vitro for 5 to 7 days (data not shown). This finding suggested that selection of EPCR ϩ cells within the CD48 Ϫ CD150 ϩ fraction (E-SLAM cells) might allow fetal and adult HSCs to be purified using the same simple protocol.…”
Section: Selective Purification Of Hscs With Durable Self-renewal Fromentioning
confidence: 96%
See 1 more Smart Citation
“…[5][6][7] Gene expression studies have revealed important insights into how biological processes are regulated at the transcriptional level in haematopoietic stem and progenitor cells (HSPC). [8][9][10] However, the global molecular mechanisms acting during physiological HSC commitment remain elusive. In a recent resource study, we investigated the global molecular mechanisms acting during physiological HSC commitment by performing an integrative analysis of proteome, transcriptome and DNA methylome, which enabled a detailed characterization of the regulatory networks active during early HSC commitment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to SH2-B and APS, Lnk is mainly expressed in haematopoietic cells, notably in haematopoietic stem cells (HSC), and haematopoietic (lymphoid and myeloid) progenitors. Moreover, Lnk expression is upregulated by certain cytokines important for the development and function of these haematopoietic cells, such as SCF, thrombopoietin [TPO], and erythropoietin [EPO] (Kent et al, 2008;Buza-Vidas et al, 2006;Gerry et al, 2009aGerry et al, , 2009bBaran-Marszak et al, 2010). Interestingly, Lnk is also highly expressed in endothelial cells and its expression is also induced by Tumor Necrosis Factor (TNF)- (Fitau et al, 2006;Kwon et al, 2009).…”
Section: Structure Origin and Cell Expressionmentioning
confidence: 99%